2008
DOI: 10.2147/opth.s4033
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid macular edema

Abstract: We review the epidemiology, pathophysiology, and etiology of cystoid macular edema (CME). Inflammatory, diabetic, post-cataract, and macular edema due to age-related macular degeneration is described. The role of chronic inflammation and hypoxia and direct macular traction is evaluated in each case according to different views from the literature. The different diagnostic methods for evaluating the edema are described. Special attention is given to fluoroangiography and the most modern methods of macula examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 80 publications
0
158
0
6
Order By: Relevance
“…On the other hand, it generally takes several months to resolve of the macular edema with these treatment modalities. Macular edema can be persistent despite these options and persistent macular edema may cause irreversible visual loss as a result of apoptosis of the photoreceptors, therefore rapid resolution of macular edema is needed [28] . Although, the mechanisms are not clear, PPV has been suggested as beneficial effects for the rapid resolution of macular edema and retinal damage in patients with RVO.…”
Section: Vitrectomy With or Without Internal Limiting Membrane (Ilm) mentioning
confidence: 99%
“…On the other hand, it generally takes several months to resolve of the macular edema with these treatment modalities. Macular edema can be persistent despite these options and persistent macular edema may cause irreversible visual loss as a result of apoptosis of the photoreceptors, therefore rapid resolution of macular edema is needed [28] . Although, the mechanisms are not clear, PPV has been suggested as beneficial effects for the rapid resolution of macular edema and retinal damage in patients with RVO.…”
Section: Vitrectomy With or Without Internal Limiting Membrane (Ilm) mentioning
confidence: 99%
“…The occurrence of CME is often associated with various vascular-inflammatory pathological conditions such as diabetic retinopathy, vein occlusion, uveitis, and commonly seen following cataract surgery in a delayed response occurring between 3-12 months. If there is a posterior capsular rupture and vitreous loss, the incidence can reach up to 20% with clinical significance [11]. While revisiting the above two refractory glaucoma cases, the root causes of CME could be one or more of the intraocular surgical complications, of which both patients had suffered, such as posterior capsule rupture, vitreous-macula traction, inflamed flat bleb, endophalmitis, or mitomycine C. Given the nature course of such intractable or refractory disease process, patients usually do not respond well to standard hypotensive medication for glaucoma.…”
Section: Revisit Rescula and Cme (Adverse Event)mentioning
confidence: 99%
“…Bevacizumab (Avastin) is a monoclonal antibody able to inactivate the effects of vascular endothelial growth factors (VEGF). The role of VEGF in pseudophakic CMO is not clear, yet several authors have reported resolution of CMO after administration of bevacizumab (55) retrospectively. This class of drugs could be of benefit in patients with chronic CMO that have exhibited a steroid hypertensive response to topical or periocular steroids.…”
Section: Cystoid Macular Oedema (Cmo)mentioning
confidence: 99%